Mg Doped Li–LiB Alloy with In Situ Formed Lithiophilic LiB Skeleton for Lithium Metal Batteries. Issue 6 (9th January 2020) - Wu, Chen; Huang, Haifeng; Lu, Weiyi; Wei, Zengxi; Ni, Xuyan; Sun, Fu; Qing, Piao; Liu, Zhijian; Ma, Jianmin; Wei, Weifeng; Chen, Libao; Yan, Chenglin; et al.
Abstract: High energy density lithium metal batteries (LMBs) are promising next‐generation energy storage devices. However, the uncontrollable dendrite growth and huge volume change limit their practical applications. Here, a new Mg doped Li–LiB alloy with in situ formed lithiophilic 3D LiB skeleton (hereinafter called Li–B–Mg composite) is presented to suppress Li dendrite and mitigate volume change. The LiB skeleton exhibits superior lithiophilic and conductive characteristics, which contributes to the reduction of the local current density and homogenization of incoming Li + flux. With the introduction of Mg, the composite achieves an ultralong lithium deposition/dissolution lifespan (500 h, at 0.5 mA cm −2 ) without short circuit in the symmetrical battery. In addition, the electrochemical performance is superior in full batteries assembled with LiCoO2 cathode and the manufactured composite. The currently proposed 3D Li–B–Mg composite anode may significantly propel the advancement of LMB technology from laboratory research to industrial commercialization. Abstract : A Li–B–Mg composite with in situ formed 3D LiB fiber network shows a dendrite‐free morphology and less volume change during cycling. The symmetrical battery achieves a long and stable cycle lifespan of more than 500 h at 0.5 mA cm −2 due to the effect of skeleton and the addition of Mg. The full battery also displays improved electrochemical performance.